The Long Wind of Change. Educational Impacts on Entrepreneurial Intentions - Robert Gold; Oliver Falck; Stephan Heblich (European Regional Science Association (ERSA), 2011)
In this paper, we assess educational factors which might have an impact on entrepreneurship. We analyze influences on the entrepreneurial intentions of German university students and find that pre-university education significantly affects their desire to become an entrepreneur. Using the recent German history of separation and reunification as quasi-natural experiment, we focus on the early formation of entrepreneurial endowments during adolescence and investigate whether pre-university education affects university students' entrepreneurial intentions. Particularly, we analyze the impact of socialization and schooling under the socialist regime of the former German Democratic Republic (GDR) which might hamper entrepreneurship. Our results show that socialist education has a negative effect on the entrepreneurial intentions of students in reunified Germany who were brought up in the GDR. When analyzing the subsample of East German students who were partly educated in the FRG after reunification in 1990, we find that some years of education in the liberal market system increase the entrepreneurial intentions of students born in the GDR. We focus on university students, since universities are seen as potential "breeding ground" for innovative entrepreneurship as described by Schumpeter (1912). Here we assume according to Falck et al. (2009) that entrepreneurial intentions are a good predictor for future entrepreneurship. We use data from a regularly repeated survey among university students in Germany. Our analysis rests on the three waves conducted after reunification at 23 universities, in (the former socialist) East as well as in West Germany. Generally, German students have significantly lower entrepreneurial intentions when they were educated in the GDR. We further restrict our sample to mobile students at West German universities and still find a negative effect of socialist education. This effect is also robust to the inclusion of a rich set of control variables concerning the students' family background, job experience as well as further measures for their educational training. Overall, being educated in the socialist GDR decreases the likelihood of having entrepreneurial intentions between around 4 and 7 percentage points Thus our findings suggest that adolescents' education might act as effective measure to stimulate entrepreneurship.
Keywords: 330